2009
DOI: 10.1021/ef900150p
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Asphaltene Precipitation from Crude Oil Blends

Abstract: A previously developed regular solution model was adapted to predict the onset and amount of asphaltene precipitation from crude oil blends diluted with pure n-alkanes or a mixture of toluene and n-heptane. Tests were conducted on nine different crude oils, a gas oil, and their blends. Oils and blends were characterized in terms of SARA (saturates, aromatics, resins, and asphaltenes) fractions. The mass fraction of each SARA fraction in the blends was confirmed as a weight average of the respective fraction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…The Athabasca bitumen and topped light crude oil are henceforth referred to as samples 1 and 2, respectively. Saturates, aromatics, resins, and asphaltenes (SARA) analysis was performed on each sample using a modified American Society for Testing and Materials (ASTM) method 11 (Table 1). The water content of samples 1 and 2 was determined by Karl Fischer titration and found to be 0.5 and 0.4 wt %, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The Athabasca bitumen and topped light crude oil are henceforth referred to as samples 1 and 2, respectively. Saturates, aromatics, resins, and asphaltenes (SARA) analysis was performed on each sample using a modified American Society for Testing and Materials (ASTM) method 11 (Table 1). The water content of samples 1 and 2 was determined by Karl Fischer titration and found to be 0.5 and 0.4 wt %, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The probability density function, p(x), is expressed as where M avg is the average molar mass of asphaltenes and α can be determined by fitting experimental data of asphaltene distributions. For asphaltenes and bitumens, Tharanivasan et al (2009) found α = 3.5. We also used this value in this paper.…”
Section: Characterization Of Asphaltenes and Determination Of Parametmentioning
confidence: 94%
“…However, there still exist uncertainties in the characterization of asphaltenes. On the other hand, the Flory-Huggins regular solution model has been largely and successfully employed to model asphaltene precipitation (flow assurance) issues (Akbarzadeh et al 2004;Alboudwarej et al 2003;Wang and Buckley 2001;Mohammadi and Richon 2007;Tharanivasan et al 2009). Nevertheless, the PC-SAFT EOS and the Flory-Huggins type of solubility model have not been extended to modeling asphaltene distributions in oil columns.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, asphaltene precipitation may occur and plug up wellbores or transfer pipelines due to temperature and pressure differences between underground reservoir and surface atmosphere . Techniques for enhanced oil recovery, that is, gas or CO 2 injection, and blending of petroleum from different wells may also cause asphaltene precipitation due to the liquid phase composition change. Besides the adverse effects during upstream production and midstream transportation, asphaltene precipitation may also lead to fouling in downstream unit operations and catalysts poisoning in fluidized cracker .…”
Section: Introductionmentioning
confidence: 99%